Use of closed suction drainage after primary total hip arthroplasty: a prospective randomized controlled trial - Lorenzo Fagotti; Leandro Ejnisman; Helder de Souza Miyahara; Henrique de Melo Campos Gurgel; Alberto Tesconi Croci; Jose Ricardo Negreiros Vicente (Revista Brasileira de Ortopedia)
ABSTRACT Objective: This study aimed to investigate drain use in a controlled population of patients with hip osteoarthritis undergoing primary total hip arthroplasty. Methods: This prospective controlled trial evaluated 93 patients randomized into two groups: a group that received drains and a group that did not. The patients who were randomized to the drain group used a 3.2 mm drain placed under the fascia that was kept in place for 24 h. Postoperative evaluations were performed after 24 h and then three, six, and 12 weeks after total hip arthroplasty. The primary outcome was perioperative blood loss in both groups 24 h after total hip arthroplasty. The other parameters that were evaluated included mid-thigh circumference, the rate of blood transfusion, hematocrit, inflammatory serum levels, and the Harris Hip Score. Results: The clinical and laboratory data revealed no differences between the study groups with respect to blood loss and need for blood transfusion, duration of hospital stay, reoperation rate, complications, inflammatory serum markers, and the Harris Hip Score. Patients without closed suction drainage reported higher pain levels after 24 h (VAS score 1 vs. 2, p < 0.01). Conclusion: Similar clinical and laboratory outcomes were found in both cohorts.